Valuing companies in transition - Schoenmaker, Dirk; Schramade, Willem (Sustainability Letters, 2022)
Transition management and corporate finance are separate disciplines. This article connects the two disciplines by developing a model of expected transition losses. It appears that adaptation to transition is a key determinant of a company’s long-term value. Companies that are early in the game can reap the first mover benefits. Companies that adapt later experience higher adaptation costs and may even not survive. The transition model helps companies to sharpen their strategy and cope with major sustainability transitions that are currently happening.